Optimization and assessment of solar-assisted cooling systems: A multicriteria framework and comparative study - Dana, Alghool (2024)
In the current context of global warming, where district cooling systems are increasingly burdening power grids worldwide, it is important to design and operate alternative systems that are not only environmentally friendly, but also cost effective for sustainable energy transition. This paper investigates the potential of two, previously unexplored, solar cooling systems while considering economic and environmental criteria: a Solar Thermal and Electrical Cooling System (STECS) that relies solely on solar energy, offering a significant environmental advantage, and a Hybrid Solar Cooling System (HSCS) that combines a compression chiller and an absorption chiller for improved efficiency. First, novel Mixed-Integer Linear Programming models are proposed to aid in generating cost-effective designs and operations for each of STECS and HSCS. Second, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is adapted to evaluate both systems and benchmark them against conventional cooling systems previously studied in the literature. The proposed framework allows decision makers to assess the potential of these systems using three criteria; namely, cost, carbon dioxide emissions, and noise levels, which are crucial for ensuring the social acceptance of district cooling technologies worldwide. A computational study is presented to show the practical relevance of the proposed framework using real-demand data obtained from an educational district in the State of Qatar. Results show that the integration of solar energy into conventional cooling systems has the potential to significantly reduce the annual total net cost by 61%, CO2 emissions by 60%, and noise levels by 53%, on average. Additionally, the benchmark results demonstrate that the zero-carbon dioxide emissions solar cooling system achieves the highest overall performance score when all criteria are considered together.